Stakeholder level: Impact of EQF on qualifications systems / potential creation of NQFs : TransEQFrame Work package 5 : Synthesis Report. - Luomi-Messerer, Karin [Verfasser]; Prokopp, Monika [Verfasser] (3s Unternehmensberatung, 2008)
"In the framework of the Leonardo da Vinci project TransEQFrame, seven countries (Austria, Bulgaria, Denmark, Finland, Germany, Netherlands and Switzerland) are exchanging opinions and reflecting on the implementation of the European Qualifications Framework (EQF). This synthesis report is the result of Work Package 5 which focused on the "stakeholder level' and in particular on the potential EQF impact on the national qualifications systems and the consequences for the development of NQFs from the stakeholders perspective. Stakeholders in this context are those at the 'second level' (different than those of WP 3: Policy level). They are responsible for qualifications on the national level (highest level of responsibility) and they are concerned with the implementation of the EQF and the (potential) creation or implementation of the NQF. The TransEQFrame project team took the following approach: First, certain aspects of implementing the EQF and the possible development of an NQF were discussed in similarly structured procedures with stakeholders in the partner countries. Second, these discussions were presented in country reports and then analysed and discussed at a two-day partner meeting in Vienna in January 2008. The synthesis report builds on the country reports and on the outcomes of the discussions at the Vienna meeting and is structured into the following sections: _ Analysis of the country reports (Section 2); _ Summary of the group discussions at the partner meeting (Section 3); _ Conclusions and recommendations (Section 4)." (ÖIBF, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; Berufliche Qualifikation; Europäischer Qualifikationsrahmen; Nationaler Qualifikationsrahmen; Europa; Österreich; Bulgarien; Dänemark; Finnland; Bundesrepublik Deutschland; Niederlande; Schweiz